The Death Ritual of Mosalaki PU'U (Leading Traditional Figure) form Respect to the Ancients of The Wolotopo Traditional Community - Karolus Charlaes Bego (Universitas Syiah Kuala, 2022)
The Indonesian people should be proud of the diverse cultures that we have. That pride must last forever, the Indonesian people must be good at taking care of their culture. Do not expect other people to love and admire our culture, therefore we ourselves must maintain and care for our culture. The implementation of the death ritual of Mosalaki Puu (Traditional Leader Leader) is a form of respect for the ancestors of the Wolotopo indigenous people, which has been inherited from generation to generation. The results of the study found that when Mosalaki Puu (Traditional Leader Leader) died, there were several rituals carried out, namely 1) beating the gong, 2) washing the corpse, 3) bending the corpse's legs and wearing oversized clothes, 4) honoring the corpse, 5) procession of the corpse towards grave pits, and 6) burial of bodies. The meaning contained in some of the rituals of death rituals.